O Chat GPT como Iceberg Digital – considerações educacionais - Edgar Lyra (O Que Nos Faz Pensar)
Teaching and research institutions received the popularization of LLMs (Large Language Models) at the end of 2022 with a mix of alarm and excitement. This article advances an interpretation and a possible reaction to the phenomenon. The hypothesis is that the ability of these devices to meet very diverse cognitive demands opens an unusual window of opportunity to rethink both the production of knowledge and the current teaching and learning practices. The prospect of accelerated and continued improvement of these technologies makes such reflection still more strategic and urgent.